2020
DOI: 10.1208/s12248-020-00550-0
|View full text |Cite
|
Sign up to set email alerts
|

Spinach and Chive for Kidney Tubule Engineering: the Limitations of Decellularized Plant Scaffolds and Vasculature

Abstract: Tissue decellularization yields complex scaffolds with retained composition and structure, and plants offer an inexhaustible natural source of numerous shapes. Plant tissue could be a solution for regenerative organ replacement strategies and advanced in vitro modeling, as biofunctionalization of decellularized tissue allows adhesion of various kinds of human cells that can grow into functional tissue. Here, we investigated the potential of spinach leaf vasculature and chive stems for kidney tubule engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Thus, optimization and alternative protocols have been explored (Table 1). Amazon sword [55], Anthurium [35], Anthurium (queen) [35], Apple interior [24,32,33,53,56], Asparagus [56], Bamboo [31,35], Basil [55], Broccoli stem [52,56], Cabbage [57], Calathea zebrina [35], Carrot [52,56], Celery [53,56,58], Cucumber [56], Ficus hispida [59], Garcinia [59], Green onion [56,60], Impatiens capensis [35], Jujube [52], Leek [61], Lucky bamboo [55], Orchid pseudobulb [35], Pachira aquatica [59], Parsley stem [34,58], Peanut hairy root [34], Persimmon [52], Potato [56], Solenostemon "wasabi" [35], Spinach [34,54,55,58,60,62,63], Sweet yellow bell pepper [52], Sweet wormwood …”
Section: Alternative Strategies To Current Chemical Decellularization Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, optimization and alternative protocols have been explored (Table 1). Amazon sword [55], Anthurium [35], Anthurium (queen) [35], Apple interior [24,32,33,53,56], Asparagus [56], Bamboo [31,35], Basil [55], Broccoli stem [52,56], Cabbage [57], Calathea zebrina [35], Carrot [52,56], Celery [53,56,58], Cucumber [56], Ficus hispida [59], Garcinia [59], Green onion [56,60], Impatiens capensis [35], Jujube [52], Leek [61], Lucky bamboo [55], Orchid pseudobulb [35], Pachira aquatica [59], Parsley stem [34,58], Peanut hairy root [34], Persimmon [52], Potato [56], Solenostemon "wasabi" [35], Spinach [34,54,55,58,60,62,63], Sweet yellow bell pepper [52], Sweet wormwood …”
Section: Alternative Strategies To Current Chemical Decellularization Protocolmentioning
confidence: 99%
“…To develop a more complete cellular model, re-endothelialization of the vascular network has been attempted. However, the recellularization of these delicate biological microfluidic systems has proven to be challenging [60]. Cell injection by hand via syringe may generate a too high flow rate and lead to an increased internal pressure that would likely damage the scaffold.…”
Section: Figurementioning
confidence: 99%
“…In vitro experiments show the promising potential application of plant-derived scaffolds. (Gershlak et al, 2017;Robbins et al, 2020) All of the research papers are in vitro experiments except our preliminary research (Lacombe et al, 2020;Jansen et al, 2020;Bai et al, 2021a). Compared to current prosthetic grafts, plant-derived scaffolds are widely available, much cheaper, and are free of animal-transmitted disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jansen et al found that the vascular system of plant leaves might not be suitable for recellularization. Although cells can grow in the petiole, they cannot enter the vascular system of leaves through the petiole because the vascular is actually located in the parenchyma near the petiole and is not connected to the petiole cavity ( Jansen et al, 2020 ). Therefore, although plant decellularized scaffolds have some similarities with human organs in general morphology, they still have slight differences, resulting in the fact that only simple-structured organs and tissues can be republicated.…”
Section: Mechanical Properties and Structures Of Decellularized Plant Scaffoldsmentioning
confidence: 99%